Implementasi Freepik untuk Peningkatan Kualitas Konten Digital Marketing Menuju UMKM 5.0 Desa Banaran - Eko Saputro; Indriyanti, Indriyanti; Meyliana, Anastasia; Andriani, Anik (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
Banaran Village, which is located in Kulon Progo Regency, has several Micro, Small and Medium Enterprises including Batik, handicraft accessories, and culinary delights consisting of smoked catfish, crispy eel, krasikan, wajik klethik, geplak, gethuk, traditional herbal medicine, cassava croquettes, and so on. Technology integration is emphasized in Micro, Small and Medium Enterprise activities which aim to increase efficiency, competitiveness and have a positive impact on society and the environment. The problem currently is that there are quite a lot of Micro, Small and Medium Enterprises in Banaran Village, but most of the products of Micro, Small and Medium Enterprises are still unknown to the wider community. Judging from product marketing activities, most Micro, Small and Medium Enterprises are still not optimal in utilizing digital marketing. Apart from the marketing method, the marketing content also still does not attract buyers' interest. The solution offered to Community Service partners is in the form of increasing the ability of Banaran Village Micro, Small and Medium Enterprises to utilize technology, especially AI tools. The activities carried out began with a survey of partner needs, continued with a workshop introducing Freepik and Digital Marketing and the next stage was the implementation of Freepik to create digital marketing content. As a result of this service, it is hoped that participants will be able to utilize Freepik and other AI tools to improve the quality of digital marketing content. The resulting digital marketing content becomes more interesting and high quality.